2011
DOI: 10.1186/1472-6831-11-5
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of orofacial clefts in Tanzania

Abstract: BackgroundClefts of the lip (CL), the palate (CP), or both (CLP) are the most common orofacial congenital malformations found among live births, accounting for 65% of all head and neck anomalies. The frequency and pattern of orofacial clefts in different parts of the world and among different human groups varies widely. Generally, populations of Asian or Native American origin have the highest prevalence, while Caucasian populations show intermediate prevalence and African populations the lowest. To date, litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
37
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 35 publications
22
37
1
4
Order By: Relevance
“…[11] Both the syndromic and asyndromal forms of CL/P may have genetic basis, as according to Stainer and Moore; [12] Ghassibe, et al, [13] several causative genes for the syndromic forms have been identified, and there is evidence that these genes also contribute to the occurrence of isolated (asyndromal) forms. However, some syndromal cases of CL/P may be non chromosomal in etiology.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[11] Both the syndromic and asyndromal forms of CL/P may have genetic basis, as according to Stainer and Moore; [12] Ghassibe, et al, [13] several causative genes for the syndromic forms have been identified, and there is evidence that these genes also contribute to the occurrence of isolated (asyndromal) forms. However, some syndromal cases of CL/P may be non chromosomal in etiology.…”
Section: Discussionmentioning
confidence: 97%
“…In previous Nigerian and Tanzanian reports, CL/P occurring in association with other anomalies such as Van der Woude's syndrome, Down's syndrome and congenital heart defects, neural tube defects, Talipes and persistent ductus arteriosus have been recorded. [3,4,11] Zimpfer, et al, [15] reported on a male fetus with bilateral brachial Amelia, complex facial clefts, frontal craniosynostosis and hypoplasia, thoracic kyphoscoliosis, and holoprosencephaly. In addition, an interrupted aortic arch, a muscular ventricular septal defect, and a localized non-compaction of the septal myocardium were present.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have addressed facial shape variation associated with CL/P in Caucasian populations [6,7,15,16], in which the prevalence of clefts is 0.91 to 2.69 per 1000 live births [17,18]. However, there have been no reported studies of facial shape in individuals with CL/P in African populations, in which the prevalence of CL/P is considerably lower, 0.3 per 1,000 to 1.65 per 1,000 live births [19,20], and the proportions of cleft types is also somewhat different [21], perhaps reflecting different underlying genetic and environmental aetiologies.…”
Section: Introductionmentioning
confidence: 99%
“…8 BCLP is seen less commonly than unilateral cleft lip and palate. 9,10 Few studies pertain to BCLP, and changes in upper-airway dimensions in subjects with BCLP have not been investigated comprehensively. Studies on airways have focused on either unilateral [11][12][13] or mixed samples of patients with cleft lip and palate [14][15][16] or adult BCLP patients.…”
mentioning
confidence: 99%